Gastric emptying, intestinal absorption of electrolytes and exercise performance in electrolyte-supplemented horses - Lindinger, M. I.; Ecker, G. L. (Experimental Physiology, 2013)
Horses lose considerably more electrolytes through sweating during prolonged exercise than can be readily replaced through feeds. The present study tested an oral electrolyte supplement (ES) designed to replace sweat electrolyte losses. We measured gastric emptying of 3 litres of ES (using gamma imaging of 99Tc-sulfide colloid), the absorption of Na+ and K+ from the gastrointestinal tract using 24Na+ and 42K+, and the distribution of these ions in the body by measuring radioactivity within plasma and sweat during exercise. Three litres of ES emptied from the stomach as fast as water, with a half-time of 47 min, and appeared in plasma by 10 min after administration (n = 4 horses). Peak values of plasma 24Na+ and 42K+ radioactivity occurred at 20-40 min, and a more rapid disappearance of K+ radioactivity from plasma was indicative of movement of K+ into cells (n = 3 horses). In a randomized crossover experiment (n = 4 horses), 1 h after administration of placebo (water), 1 or 3 litres of ES containing 24Na+, horses exercised on a treadmill at 30% of peak oxygen uptake until voluntary fatigue. The 24Na+ appeared in sweat at 10 min of exercise, and when horses received 3 litres of ES the duration to voluntary fatigue was increased in all horses by 33 ± 10%. It is concluded that an oral ES designed to replace sweat ion losses was rapidly emptied from the gastrointestinal tract, rapidly absorbed in the upper intestinal tract and rapidly distributed within the body. The ES clearly served as a reservoir to replace sweat ion losses during exercise, and administration of ES prior to exercise resulted in increased duration of submaximal exercise.